Recovery of Gold and Silver from Metallurgical Slags Using Industrial Scale Shaking Tables - Aıta, Mohamed Saleh Mohamed; Hacıfazlıoğlu, Hasan (Fırat University, 2025)
In this study, the recovery of gold and silver remaining in the metallurgical slag using the gravity method, which is an environmentally friendly method, was investigated. For this purpose, two different industrial-scale gravity devices were used. Coarse enrichment was applied with the classic shaking table, and the concentrate was cleaned with the Gemini table. Additionally, various operating parameters have been optimized in the classic shaking table for optimum recovery of gold and silver. The most ideal conditions include an appropriate combination of table inclination, table speed, feed solids rate and wash water speed. Experiments were carried out with slag sample containing 7.80 ppm Au and 131 ppm Ag. The slags were ground to below 150 ?m grain size in the ball mill and then fed into the gravity devices. In the final concentrate obtained, the Au grade was found to be 109.24 ppm and the Ag grade was 1692.71 ppm. According to the final results, 56.16% of the gold and 51.82% of the silver in the slag were recovered.

Bu çalışmada, metalurjik cüruf içerisinde kalan altın ve gümüşün çevre dostu bir yöntem olan gravite yöntemi ile geri kazanımı araştırılmıştır. Bu amaçla, endüstriyel ölçekli iki farklı gravite cihazı kullanılmıştır. Klasik sallantılı masa ile kaba zenginleştirme, Gemini masası ile konsantreye temizleme işlemi uygulanmıştır. Ayrıca, altın ve gümüşün optimum düzeyde geri kazanımı için klasik sallantılı masada çeşitli çalışma parametreleri optimize edilmiştir. En ideal koşullar; masa eğimi, masa hızı, besleme katı oranı ve yıkama suyu hızının uygun bir kombinasyonunu içermektedir. Deneyler, 7,80 ppm Au ve 131 ppm Ag içeren cüruf numunesi ile yapılmıştır. Cüruflar, bilyalı değirmende 150 ?m tane boyutunun altına öğütülmüş ve ardından gravite cihazlarına beslenmiştir. Elde edilen nihai konsantrede Au tenörü 109,24 ppm, Ag tenörü ise 1692,71 ppm bulunmuştur. Nihai sonuçlara göre, cüruf içerisindeki altının %56,16’sı, gümüşün ise %51,82’si geri kazanılmıştır.
Metalurjik Cüruflardan Altın ve Gümüşün Endüstriyel Ölçekli Sallantılı Masalar ile Geri Kazanımı
Keywords: Chemical-Biological Recovery Techniques and Ore Dressing; Kimyasal-Biyolojik Kazanma Teknikleri ve Cevher Hazırlama